A systematic review to identify and assess the effectiveness of alternatives for people over the age of 65 who are at risk of potentially avoidable hospital admission. Issue 7 (1st August 2017) - Huntley, Alyson L; Chalder, Melanie; Shaw, Ali R G; Hollingworth, William; Metcalfe, Chris; Benger, Jonathan Richard; Purdy, Sarah
Abstract : Background/objectives: There are some older patients who are 'at the decision margin' of admission. This systematic review sought to explore this issue with the following objective: what admission alternatives are there for older patients and are they safe, effective and cost-effective? A secondary objective was to identify the characteristics of those older patients for whom the decision to admit to hospital may be unclear. Design: Systematic review of controlled studies (April 2005–December 2016) with searches in Medline, Embase, Cinahl and CENTRAL databases. The protocol is registered at PROSPERO (CRD42015020371). Studies were assessed using Cochrane risk of bias criteria, and relevant reviews were assessed with the AMSTAR tool. The results are presented narratively and discussed. Setting: Primary and secondary healthcare interface. Participants: People aged over 65 years at risk of an unplanned admission. Interventions: Any community-based intervention offered as an alternative to admission to an acute hospital. Primary and secondary outcomes measures: Reduction in secondary care use, patient-related outcomes, safety and costs. Results: Nineteen studies and seven systematic reviews were identified. These recruited patients with both specific conditions and mixed chronic and acute conditions. The interventions involved paramedic/emergency care practitioners (n=3), emergency department-based interventions (n=3), community hospitals (n=2) and hospital-at-home services (n=11). Data suggest that alternatives to admission appear safe with potential to reduce secondary care use and length of time receiving care. There is a lack of patient-related outcomes and cost data. The important features of older patients for whom the decision to admit is uncertain are: age over 75 years, comorbidities/multi-morbidities, dementia, home situation, social support and individual coping abilities. Conclusions: This systematic review describes and assesses evidence on alternatives to acute care for older patients and shows that many of the options available are safe and appear to reduce resource use. However, cost analyses and patient preference data are lacking.